Investigation of the hepatoprotective potential of the hydroalcoholic leaves extract of Ricinus communis on isoniazid induced and thioacetamide induced hepatotoxicity in Wistar rats - Oza, Sushrut; Shelar, Reshma; Waghulde, Priyanka; Kolhe, Swati; Saldanha, Tina (International Journal of Basic & Clinical Pharmacology, 2025)
Background: The liver is highly susceptible to drug- and chemical-induced injury. Isoniazid and thioacetamide are known hepatotoxins that cause oxidative damage. R. communis leaves possess bioactive compounds with reported antioxidant and hepatoprotective potential. This study evaluated the hydroalcoholic leaf extract of R. communis against isoniazid and thioacetamide induced hepatotoxicity in Wistar rats. Methods: Wistar rats were divided into five groups in each model. Each group consisted of five animals. Hepatotoxicity was induced using isoniazid (250 mg/kg, p.o., 14 days) and in another model using thioacetamide (400 mg/kg, i.p., 3 days). Test groups received R. communis extract at 250 and 500 mg/kg, with Liv.52 (400 mg/kg) as standard. Serum hepatic markers, body weight, liver-to-body weight ratio, and liver histology were assessed. Antioxidant activity was determined by ferric reducing antioxidant power assay. Data were analyzed using one-way ANOVA followed by Tukey’s test. Results: In the isoniazid model, RIC 250 mg/kg and 500 mg/kg significantly reduced ALT levels (p<0.05), however at 500 mg/kg, the extract increased AST and ALP levels. The liver-to-body weight ratio decreased significantly in treatment groups. Histology revealed minimal hepatic changes compared to moderate-to-severe injury in controls. In the thioacetamide model, R. communis produced mild biochemical improvement but caused mortalities in both dose groups. FRAP assay confirmed antioxidant potential (EC₅₀=12.39 µg/ml). Conclusions: R. communis extract demonstrated significant hepatoprotective and antioxidant activity, particularly at 250 mg/kg. However, the inconsistent effects at a higher dose and observed mortalities in the TAA model necessitate further investigation into its safety and therapeutic window.